Sovereign wealth fund investments in private funds: selected tax planning considerations in the US, EU and UK. Issue 3 (15th July 2021) - Nelson, Daniel A.; Habershon, Kate; Hambrick, Kathryn W.; McCarthy, Meghan E.; Hadji, Alexios S.; Tan, Grace
Abstract : Purpose: To discuss US, EU and UK tax-related issues that sovereign wealth funds should consider when investing in private funds. Design/methodology/approach: Discusses various tax-related structuring, operational, risk-allocation, and economic matters that private funds, sovereign wealth funds and other non-US institutional investors should consider a series when evaluating potential private fund investments. Findings: Despite the market disruption caused by the COVID-19 pandemic, sovereign wealth funds continued to make significant capital commitments to private funds in 2020 and, as the world emerges from the pandemic, are expected to make similar or greater commitments in 2021 and beyond. Originality/value: Practical guidance from lawyers with wide experience in international tax planning and investment fund structuring.